Escherichia coli as Microbiological Quality Water Indicator:A High Importance for Human and Animal Health: Microbiological water quality - Zarić, G; Cocoli, S; Šarčević, D; Vještica, S; Prodanović, R; Puvača, N; Carić, M (Journal of the Hellenic Veterinary Medical Society, 2023)
The purpose of this review is to demonstrate the importance of monitoring microbiological quality in water for animals and humans, which relies primarily on coliforms, mostly Escherichia coli. Fecal coliforms, such as E. coli, are more specific indicators of fecal pollution. A fecal contamination detection can be performed not just in drinking water, but also in the environment. As a result of improved detection methods for E. coli, drinking water is becoming more reliable as a result of the use of E. coli as an indicator of fecal pollution. Drinking water contamination by feces is currently best detected by E. coli. Accordingly, temperate environments are more likely to have fecal coliforms than tropical environments, human and animal feces have high levels of E. coli in comparison to other fecal coliforms, and E. coli detection methods are more affordable, fast, sensitive, specific, and easy to use than other fecal coliforms.